Análisis de los factores que afectan la productividad de la central hidroeléctrica Coca Codo Sinclair - Cacao Sancán, Génesis de Jesús (2025)
There are several factors affecting the productivity of the Coca Codo Sinclair hydroelectric plant. The dam is important to provide electricity in Ecuador, especially in the face of growing industrial demand and climate changes such as rain or drought. Although it is true that it has a capacity of 1,500 MW, since it does not operate at its maximum potential due to technical failures, deficiencies in infrastructure maintenance, and variations in the flow of the Coca River, all of these factors lead to instability in the energy supply. This study highlights the importance of analyzing these factors, taking preventive measures that will help counteract these persistent risk factors, and also recognizing the challenges it faces due to climate change, water levels, aging infrastructure and maintenance. This research aims to analyze the factors that affect the productivity of the Coca Codo Sinclair hydroelectric plant in order to minimize the economic impact with the aim of reducing risk factors, through optimal strategies that improve energy efficiency. To do this, the water flow rate and the height of the fall will be examined, determining the power and the impact that it presents when there is a variation in the flow rate in order to identify the problems to discuss/analyze the productivity of the hydroelectric plant, through exercises in those the various variations with different scenarios will be reflected, to persuade how far it can be reached.